Features extraction techniques for heart sounds and murmurs - 426413 Zamri Mohd. Zain (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007